2001
DOI: 10.1007/s004170100361
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes due to drug-induced lysosomal storage of sulphated glycosaminoglycans in the rat retina

Abstract: the glycosaminoglycan storage in pigment epithelium is reminiscent of that seen in some inherited mucopolysaccharidoses of humans. When a given cell type shows lysosomal accumulation of glycosaminoglycans as a consequence of impaired degradation, it can be assumed to be engaged in the turnover of glycosaminoglycans under normal conditions. Thus the present results suggest that not only the retinal pigment epithelium but also Müller cells, photoreceptor cells, and, to variable degree, retinal neurons are normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Further studies by immunoelectron microscopy revealed that the materials in some vacuoles were immunoreactive for G M2 ganglioside. Although we have found no papers addressing the involvement of RPE cells in human G M2 gangliosidoses, the findings of the present study using a mouse model imply that ganglioside stores in RPE cells appear in the shape of 'vacuolated inclusions', as seen in inherited (mucopolysaccharidoses) [22,23] and drug-induced [24] lysosomal storage of glycosaminoglycans. Lysosomal ␤ -hexosaminidase isozymes (HexA, HexB, and HexS) play a role in the degradation of G M2 ganglioside and related glycolipids [1] , glycosaminoglycans [25] , and N-linked oligosaccharides [26,27] .…”
Section: Discussioncontrasting
confidence: 58%
“…Further studies by immunoelectron microscopy revealed that the materials in some vacuoles were immunoreactive for G M2 ganglioside. Although we have found no papers addressing the involvement of RPE cells in human G M2 gangliosidoses, the findings of the present study using a mouse model imply that ganglioside stores in RPE cells appear in the shape of 'vacuolated inclusions', as seen in inherited (mucopolysaccharidoses) [22,23] and drug-induced [24] lysosomal storage of glycosaminoglycans. Lysosomal ␤ -hexosaminidase isozymes (HexA, HexB, and HexS) play a role in the degradation of G M2 ganglioside and related glycolipids [1] , glycosaminoglycans [25] , and N-linked oligosaccharides [26,27] .…”
Section: Discussioncontrasting
confidence: 58%
“…Amiodarone, chloroamitriptyline, chlorphentermine, clomipramine, imipramine, iprindole, various aminoglycosides, and other cationic amphophilic compounds interfere with the enzymatic degradation of phospholipids. Consequently, their systemic administration results in accumulation of phospholipids in various retinal cells, including the pigment epithelium (retinal lipidosis), which is reminiscent of glycosaminoglycan storage observed in some inherited mucopolysaccharidoses (Bredehorn et al, 2001). The phospholipids are stored in abnormal cytoplasmic inclusions with crystalloid substructure and are partially reversible upon discontinuation of treatment (Lullmann-Rauch, 1976; Bockhardt et al, 1978; Drenckhahn and Lullmann-Rauch, 1978; Bockhardt and Lullmann-Rauch, 1980; Lullmann-Rauch, 1981; D’Amico et al, 1985; Tabatabay et al, 1987; Duncker and Bredehorn, 1994; Bredehorn et al, 2001).…”
Section: Toxic Effects On the Pigment Epitheliummentioning
confidence: 99%
“…Despite extensive PLD, laboratory animals generally seem to be well. However, effects on cell function are possible 92 , 93 and include impairment of cell metabolism or of pino/endocytosis. Some drugs such as propranolol and verapamil were reported to lead to lactate dehydrogenase (LDH) release from hepatocytes, while other drugs, such as chloroquine and amiodarone, may be associated with myopathy.…”
Section: Examples Of Addressing Apfsmentioning
confidence: 99%